DIABETES; A HINDRANCE IN MUSCULOSKELETAL DISEASES - Johnson, Blessy. K.; Raju, Mareena; S, Ambarish; R, Bharathii D (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Diabetes mellitus (DM) affects connective tissues in many ways and causes different alterations in periarticular and skeletal systems. Musculoskeletal complaints (MSCs) are among the major health problems worldwide and the most frequent cause of long term sickness. Objectives: To assess the prevalence, treatment pattern of musculoskeletal diseases with diabetes mellitus and to evaluate the impact of patient counselling overcome the barriers of diabetes in musculoskeletal disease. Materials & Methods: A prospective observational study was carried out for a period of six months at Departments of Orthopedic and General medicine, Basaveshwara Medical College & Research center and Ambarish’s Clinic,Chithradurga. A total of 118 subjects were included as per study criteria. Results: Among 118 subjects 17 (14.4%) had musculoskeletal manifestations with DM. The study shows that 55.9% patients were males and 44.06% were females. The maximum number of patients comes under the age of 51-60yrs.The NSAIDs prescribed were Diclofenac (8.69%), Paracetamol (8.69%) and Piroxicam 4(8.69%) and the Antidiabetic drugs in present study were Oral hypoglycemic followed by Insulin. Most of the patients are affected with Osteoarthritis (47.05%), followed by Adhesive capsulitis (11.76%) and Osteoporosis (11.76%). Conclusion: The study reveals that the prevalence of musculoskeletal disease with DM is significantly high and osteoarthritis is the common disease. Males are more affected than females with an age group of 51-60. Key words: Diabetes mellitus, musculoskeletal disease, prevalence, prescription pattern.